2014
DOI: 10.3109/02770903.2014.895010
|View full text |Cite
|
Sign up to set email alerts
|

Preventive asthma medication discontinuation among children enrolled in fee-for-service Medicaid

Abstract: More than 60% of children enrolled in fee-for-service Medicaid/CHIP discontinued preventive asthma medications by 90 d. Risk was increased for minorities and children from disadvantaged households. Understanding these factors may inform future pediatric asthma guidelines.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
29
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(30 citation statements)
references
References 38 publications
(90 reference statements)
1
29
0
Order By: Relevance
“…18 More than 60% of children covered by public health insurance discontinue prescribed asthma medications within 3 months of starting them, with minorities and children from disadvantaged families being more likely to do so. 19 Analyses from the present study show that children with asthma with public health insurance were more likely to delay or not fill prescribed medications because of cost compared to children with private insurance or the general population. Co-payments in low-income populations adversely affect the likelihood of filling prescription medications, especially in sicker individuals.…”
Section: Discussionmentioning
confidence: 81%
“…18 More than 60% of children covered by public health insurance discontinue prescribed asthma medications within 3 months of starting them, with minorities and children from disadvantaged families being more likely to do so. 19 Analyses from the present study show that children with asthma with public health insurance were more likely to delay or not fill prescribed medications because of cost compared to children with private insurance or the general population. Co-payments in low-income populations adversely affect the likelihood of filling prescription medications, especially in sicker individuals.…”
Section: Discussionmentioning
confidence: 81%
“…Third, the 2013 YRBS did not include information on prescribed asthma medication, current asthma status, or asthma severity. Research investigating the impact of medications with leukotriene modifiers such as inhalers and steroids has been of interest since the Food and Drug Administration mandated medication labels to contain information on possible suicidality in 2009 . Other researchers have observed that parents of children with harsh asthma conditions were more troubled about their children being victims of bullying .…”
Section: Discussionmentioning
confidence: 99%
“…Research investigating the impact of medications with leukotriene modifiers such as inhalers and steroids has been of interest since the Food and Drug Administration mandated medication labels to contain information on possible suicidality in 2009. [36][37][38][39] Other researchers have observed that parents of children with harsh asthma conditions were more troubled about their children being victims of bullying. 20 Thus, the ability to include more information on the medication prescribed to control asthma symptoms, asthma symptoms at the time of the survey, and severity of asthma could provide a better understanding of the relationship among having asthma, being bullied, and exhibiting suicidal ideation and/or behaviors.…”
Section: Limitationsmentioning
confidence: 99%
“…Assessing asthma severity 18 studies used 20 different algorithms to assess asthma severity (supplementary table E10) as binary (i.e. severe versus nonsevere asthma) [15,23,[25][26][27][28][29][30][31][32][33][34][35][36][37][38] or ordinal variables (mild, moderate and severe asthma [39]; low-, moderate-and high-risk asthma [40]). The algorithms were based on one or more of the following asthma-related variables: number and/or dosage of prescriptions (i.e.…”
Section: Defining Asthmamentioning
confidence: 99%